Coronavirus Anxiety Scale: New psychometric evidence for the Spanish version based on CFA and IRT models in a Peruvian sample - Caycho-Rodríguez, Tomás (2021)
The aim of the study was to analyze the psychometric properties of the Spanish version of the Coronavirus Anxiety Scale (CAS), using Item Response Theory (IRT) and Confirmatory Factor Analysis (CFA). The participants were 790 Peruvians, selected through a convenience sampling, where the majority were women. The CFA models indicated that the one-dimensional structure better represents the data, is reliable and invariant between men and women. Likewise, IRT findings indicate that CAS is more informative for high levels of COVID-19 anxiety. The CAS in Spanish has adequate psychometric properties to be used as a short measure of COVID-19 anxiety.